2015
DOI: 10.1002/qj.2522
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of kriging‐based rain‐gauge–radar merging techniques

Abstract: This article is published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.Networks of rain-gauges provide an accurate but highly localized measure of rainfall, with limited coverage and resolution, whereas radars provide rain-rate and accumulation estimates over wide areas at high spatial and temporal resolution but low accuracy. When quantifying rainfall accumulations for applications such as flood forecasting, combining the two sets of data can be beneficial for producing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
2
57
0
1
Order By: Relevance
“…Steps to simulate one realization of the system over a particular rainfall event; NEXRAD stands for next generation weather radar; SWMM stands for Storm Water Management Model; TF, MF_KED G , MF_KED CG , MF_DM 1 , MF_DM 2 and MF_FBRK are as defined in Table 1; REAA I , RMSE I , ARE P , ARE V , RMSE F and RMSE F10 are as defined in Table 3. their improvements over the MF_KED G , MF_DM 1 , and MF_DM 2 results. That the two best performing data sets are KED based is consistent with existing studies in the literature (Goudenhoofdt & Delobbe, 2009;Jewell & Gaussiat, 2015), which have found the KED method to be, in general, the most effective thus far for merging radar and rain gauge data.…”
Section: Deterministic Comparison Of the Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Steps to simulate one realization of the system over a particular rainfall event; NEXRAD stands for next generation weather radar; SWMM stands for Storm Water Management Model; TF, MF_KED G , MF_KED CG , MF_DM 1 , MF_DM 2 and MF_FBRK are as defined in Table 1; REAA I , RMSE I , ARE P , ARE V , RMSE F and RMSE F10 are as defined in Table 3. their improvements over the MF_KED G , MF_DM 1 , and MF_DM 2 results. That the two best performing data sets are KED based is consistent with existing studies in the literature (Goudenhoofdt & Delobbe, 2009;Jewell & Gaussiat, 2015), which have found the KED method to be, in general, the most effective thus far for merging radar and rain gauge data.…”
Section: Deterministic Comparison Of the Resultssupporting
confidence: 87%
“…Though, the margin of improvement of the MF_FBRK results over the MF_KED CG results is relatively minor compared to both their improvements over the MF_KED G , MF_DM 1 , and MF_DM 2 results. That the two best performing data sets are KED based is consistent with existing studies in the literature (Goudenhoofdt & Delobbe, ; Jewell & Gaussiat, ), which have found the KED method to be, in general, the most effective thus far for merging radar and rain gauge data.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In general, combining radar and rain gauge data is very difficult in the vicinity of heavy local rain cells (Einfalt et al, 2005). Recently, Jewell and Gaussiat (2015) compared performances of different merging schemas and noted a large difference between convective and stratiform situations. In their study, the nonparametric kriging with external drift outperformed other methods in an accumulation period of 60 min.…”
Section: Introductionmentioning
confidence: 99%
“…There is an abundance of literature dealing with this merging process (e.g. Collier et al 1983;Jewell and Gaussiat 2015;Velasco-Forero et al 2009;Berndt et al 2014).…”
Section: Observation Of Rainfall and Its Spatial Representation In Lamentioning
confidence: 99%